Advance Directives: Rethinking Regulation, Autonomy & Healthcare Decision-Making - Chan, Hui Yun. (Cham : Springer International Publishing, 2018)
This book offers a new perspective on advance directives through a combined legal, ethical and philosophical inquiry. In addition to making a significant and novel theoretical contribution to the field, the book has an interdisciplinary and international appeal. The book will help academics, healthcare professionals, legal practitioners and the educated reader to understand the challenges of creating and implementing advance directives, anticipate clinical realities, and preparing advance directives that reflect a higher degree of assurance in terms of implementation.
Introduction -- The making of advance directives -- Legal responses to the challenges of making advance directives -- Supported decision-making: an approach to advance directives -- A supported decision-making model for advance directives -- Regulating advance directives.
Religion and Philosophy
text file PDF
Keywords: Bioethics; Medical laws and legislation; Law-Philosophy.; Law